Speleological approach for geotourism development in Zlatibor county (West Serbia) - Vuković, Stojan; Antić, Aleksandar (Turizam, 2019)
Western Serbia is a part of the Dinaric karst, which makes this area rich with caves, karst springs, karst waterfalls and other karst phenomena. Caves in the Zlatibor county, as representative speleological geosites, are one of the first established tourist caves in Serbia. They have great potential for speleotourism and geotourism development in the region and are considered important for tourism development of Zlatibor mountain. In this paper we analyze the speleological potential for geotourism development in Zlatibor county (west Serbia). The main goal of the paper was to determine the current state of geotourism in Zlatibor county and possibilities for further development by analyzing two caves in this area: Stopića cave and Potpećka cave. Our research was carried out by applying the Modified Geosite Assessment Model (M-GAM). The results show that these caves are not just favourable geosites with great complementary tourism potential of the Zlatibor mountain, but they are also unique speleological objects with a vast speleotourism and geotourism development opportunities.